PENERAPAN MODEL REALISTICS MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA di SDN NO 100615 SIGALANGAN - Mona Vebyani; Amirullah Husin; Rama Nida Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve mathematics learning outcomes in second-grade students at SDN No. 100615 Sigalangan in the topic of integer arithmetic operations using the RME Model. The methodology applied in this study is the Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model which took place in two cycles, involving 19 students from second grade. The results of the study showed significant growth and overall achievement. The successful implementation of RME learning by teachers obtained an average score of 3.51 (Well Met), supported by very positive student responses with an average reaching 88.42%. The improvement in learning outcomes is seen from the surge in the percentage of classical completeness which increased from 52.63% (Cycle I - Poor) to 94.73% in Cycle II (Very Good Category), with an average post-test score increasing to 90.52. Therefore, the implementation of the RME Model has proven effective and successful in improving the mathematics learning outcomes of second- grade students at SDN No. 100615 Sigalangan.